Landscape considerations in spatial planning. - Belcáková, Ingrid; Laszlo, Miklos; Spinerová, Anna; Diviaková, Andrea; Kocická, Erika; Belanová, Eliska (Lang, 2019)
The landscape is a vital spatial and material frame for our natural and man-made environment and is considered by many stakeholders to be one of the most important aspects of a healthy, enjoyable life. This book deals with the current trends in the theory of the integration of landscape aspects in spatial planning and development processes. The authors discuss the need for integrated land use planning, landscape planning and impact assessment, and explore landscape consideration practice in European countries, with a special focus on Slovakia. Information about landscape decision-making approaches and cases illustrates current practice and lessons from experience, providing baseline material for landscape academic forum, members of the public and professionals in spatial development making: planners, designers, architects, engineers and others. This practice-oriented and up-to-date monograph is a sourcebook and reference guide to key trends, issues of and approaches to sustainable spatial development in European countries.
Keywords: Raumplanung; Regionalentwicklung; Nachhaltige Entwicklung; Ländlicher Raum; Landschaftsplanung; Ökologie; Landnutzung; Landwirtschaft